TOPSIS Method In Determining The Best Package Transportation Route - Taymour A. Hamdallah; Mohammad Badri; Wahyu Caesaendra; Antoni Pribadi; Yustria Handika Siregar; Tasya Annisa S (Journal of Information Systems and Technology Research, 2025)
The urgent need for product transportation services during the ongoing pandemic has prompted companies to organize transportation processes effectively to ensure customers are well served. The increase in demand for goods transportation services has been driven by the pandemic, as it has necessitated social distancing and adherence to health protocols. Traditionally, transportation services rely on distance calculation technologies to determine the best route for delivering packages, which may reduce transportation efficiency. One example is the delivery service at J&T Sidamukti drop point by PT Tiki Lintas. This research aims to provide an overview of the steps involved in using the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method to determine the optimal transportation route for package delivery. The use of the TOPSIS method in this study aims to improve the efficiency of transportation time by evaluating and comparing different delivery routes based on multiple criteria. Through this approach, the study intends to highlight how optimal decision-making processes can enhance the efficiency of goods transportation in a challenging context like the pandemic. The research also seeks to offer practical solutions that can be applied to similar transportation challenges, thereby contributing to the overall improvement of delivery systems. Ultimately, the findings of this study are expected to provide valuable insights into the application of decision-making models in transportation route planning, particularly in the current context of limited movement and physical distancing.